MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN SEJARAH KEBUDAYAAAN ISLAM (SKI) MELALUI METODE PEMBELAJARAN MIND MAPPING - Karim, Abdul (Pascasarjana IAIN Kudus, 2013)
Saturated Attitude in learning is one problem that leads decreasing student motivation in the History of Islamic Culture (SKI), it mustbe solved. This study found that mind mapping of SKI materialcourse can be an alternative solution to solve it. The objectivewas to obtain an overview of the implementation of learning mindmapping relation to student motivation sixth semester 2012/2013Program PAI in Tarbiyah STAIN Kudus on SKI material course.Data were taken from PAI students of class A, with classroomaction research (CAR). To get the complete data, the study useda qualitative approach to retrieve, analyze, and process data andinformation to be concluded in order to answer the problem that isbeing studied. The results showed that, the implementation methodsof learning mind mapping on SKI, success: (1) improve studentlearning motivation, (2) increased student activity and make quality, and (3) increased student learning to make creative and varied.